The role of atorvastatin in bone metabolism in male albino Wistar rats - Gradosova, I; Zivna, H; Svejkovska, K; Palicka, V; Tichy, A; Zivny, P (Die Pharmazie, 2011)
OBJECTIVE: Statins have been widely used for the treatment of hypercholesterolemia, and recent studies have shown that these drugs also affect bone metabolism. The aim of this experiment was to follow the effect of atorvastatin on bone metabolism in male albino Wistar rats. METHODS: Our study was carried out on 16 rats (240 +/- 10g) which were randomly divided into 2 groups of 8 animals. The control group (CO) was given aqua pro injectione (0.2 mL/100 g BW; gavage) and the experimental group atorvastatin suspension (AT; 0.3 mg in 0.2 mL aqua pro inj./100 g BW; gavage) daily for 8 weeks. We examined serum markers of bone turnover using ELISA - C-terminal crosslinking telopeptide of type I collagen (CTX-I), total osteocalcin (total OC), procollagen type I N propeptide (PINP) and bone alkaline phosphatase (bone ALP). We investigated bone morphogenetic protein-2 (BMP-2) in the proximal tibia using Western blot analysis. Additionally, we measured bone mineral density (BMD). The femurs were used for a three-point bending test and compression test of the femoral neck. RESULTS: After 8 weeks of atorvastatin administration, a significant decrease was found in serum level of bone ALP to 30% vs. CO (p = 0.005). PINP, CTX-I and OC did not change significantly. The expression of BMP-2 was increased. There were no significant differences in BMD measurements, three-point bending test or compression test of the femoral neck. CONCLUSIONS: Our results suggest that atorvastatin has a positive effect on bone metabolism in rats by maintenance of BMD and the biomechanical characteristics of bone. Atorvastatin influenced bone metabolism by decreasing bone ALP, and probably in consequence increasing expression of BMP-2 in rats.
Keywords: Animals; Electrophoresis, Polyacrylamide Gel; kolagen typu I; Procollagen; Rats; absorpční fotometrie; prenylace proteinů; Rats, Wistar; biologické markery; Blotting, Western; Absorptiometry, Photon; Biomarkers; kostní denzita; Bone Density; kosti a kostní tkáň; osteokalcin; alkalická fosfatasa; Heptanoic Acids; osteoprotegerin; Osteocalcin; Bone Morphogenetic Protein 2; kostní morfogenetický protein 2; statiny; peptidové fragmenty; biomechanika; western blotting; Male; Hydroxymethylglutaryl-CoA Reductase Inhibitors; Peptide Fragments; Pyrroles; kyseliny heptylové; krysa rodu Rattus; Alkaline Phosphatase; Protein Prenylation; zvířata; mužské pohlaví; Collagen Type I; elektroforéza v polyakrylamidovém gelu; Bone and Bones; pyrroly; Osteoprotegerin; Biomechanical Phenomena; prokolagen; potkani Wistar